Serum Calcitonin Gene-Related Peptide and Receptor Protein Levels in Patients With Fibromyalgia Syndrome: A Cross-Sectional Study - Ragıp Ulvi KORUCU,; Ahmet KARADAĞ,; Ayça TAŞ,; Esma ÖZMEN,; Emrullah HAYTA,; Yavuz SILIĞ, (Archives of Rheumatology, 2020)
Objectives: This study aims to compare the serum calcitonin gene-related peptide (CGRP) and CGRP receptor protein levels between patients with fibromyalgia syndrome (FM) and healthy control subjects. Patients and methods: The study included 88 patients (7 males, 81 females; mean age 44.5±9.1 years; range, 20 to 72 years) newly-diagnosed with FM according to the 2010 American College of Rheumatology criteria and 88 healthy volunteers (6 males, 82 females; mean age 43.0±6.1 years; range, 20 to 57 years). Venous blood samples were collected from both groups for the measurement of the levels of serum CGRP and CGRP receptor proteins (receptor component protein [RCP], receptor activity modifying protein 1 [RAMP 1] and calcitonin receptor-like receptor [CLR]). Results: A comparison of the serum CGRP, CLR and RCP levels of the FM and control groups revealed a statistically significant difference (p=0.001, p=0.005, p=0.001, respectively). The difference between the groups in respect of the serum RAMP 1 levels was not statistically significant (p=0.107). Conclusion: The serum CGRP, CLR and RCP levels were found to be higher in the FM patients, but no difference was determined between the FM patients and the healthy control group in respect of the RAMP 1 level. These results can be of guidance for further clinical studies of the etiopathogenesis and treatment of FM.